The Liquid Droplets Evapo¬ration for Low Pressure’s Values under Low-power Irradiation with Different Frequencies at the Optical Range - Brytan, A.V.; Verbinska, G.M.; Sysoev, V.M.; Karbovskiy, V.L.; Cleshchonok, T.V. (Ukrainian Journal of Physics, 2022)
The results of experimental researches concerning the influence of optical radiation with various frequencies (wavelengths of 390, 565, and 625 nm) on the droplet evaporation rate in the atmosphere of dry nitrogen at pressures of 30, 50, and 100 mm Hg and the temperature of a vapor-gas mixture of 20 ºC, which were obtained for a number of liquids, are reported. A substantial increase of the evaporation rate for water (up to 25%), nitrobenzene (up to 40%), and iodobenzene (up to 60%) droplets at a constant droplet temperature during the evaporation has been detected. The evaporation rates for ethyl benzene and isoamyl alcohol droplets in the dark regime and under radiation are found invariable within the limits of experimental errors. The red threshold of this effect is observed.